Uma abordagem apoiada por linguagens especificas de domínio para criação de linhas de produtos de software embarcado - Durelli, Rafael Serapilha (2011)
Embedded systems have been used in a myriad of devices that are present in our daily lives, thereby the market for such sort of system has increased significantly over the last few years. These systems were once associated with low-level code, however, this is an outdated view of embedded systems technology. Although the current embedded systems are mostly composed of software, no systematic reuse technique is used in throughout their development. Thus, since previous successful experiences are not reused, forcing the developer to create some of the involved elements from the scratch, there is a considerable delay in the production of these systems. Due to the ever increasing complexity of embedded systems it is necessary to apply reuse techniques in order to lessen the effort needed to develop such systems. Within this context, software product lines (SPL) are reuse techniques that allow the creation of several systems belonging to a certain domain. SPL can be used to generate products of a specific domain that share common features but are each different in a specific way. Model-driven development is another reuse technique whose main objective is to reduce the semantic distance between the domain problem and its solution/implementation; thus, the developer does not need to direct interact with the solution source code, being able to focus on models and transforming those models in source code or yet other models. Based on these techniques, a process for the development of SPL in the domain of mobile robots was developed. In order to properly use the proposed process, a SPL called LegoMobileRobots Software Product Line (LMRSPL) was devised. Moreover, a domain specific language (DSL) was also developed. This DSL, called F2MoC, assists the application engineer in instantiating LMRSPL members.